2000
DOI: 10.4049/jimmunol.165.12.7199
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL-6 and IL-8 Expression in Rheumatoid Arthritis Synovial Fibroblasts: the Dominant Role for NF-κB But Not C/EBPβ or c-Jun

Abstract: Rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLS) produce IL-6 and IL-8, which contribute to inflammation and joint damage. The promoters of both cytokines possess binding sites for NF-κB, C/EBPβ, and c-Jun, but the contribution of each to the regulation of IL-6 and IL-8 in RA FLS is unknown. We employed adenoviral-mediated gene delivery of a nondegradable IκBα, or dominant-negative versions of C/EBPβ or c-Jun, to determine the contribution of each transcription factor to IL-6 and IL-8 expression. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(148 citation statements)
references
References 52 publications
11
135
1
1
Order By: Relevance
“…Baicalein inhibits CCAAT/enhancer binding protein b (C/EBPb) DNAbinding activity in COX-2 promoter region and suppresses COX-2 expression in mouse macrophages, 18) while C/EBPb plays no or little role in IL-6 and IL-8 transcription in LPStreated dermal fibroblasts and LPS-treated rheumatoid arthritis synovial fibroblasts. 22) Taken together, our results suggest that the mechanism of anti-inflammatory effects of TJ-9 is mainly the suppression of PGE 2 production rather than those of inflammatory cytokines. Moreover, this decreased PGE 2 production will cause substantial reduction of PGE 2 in periodontal tissue because periodontal tissue is mainly occupied by HGFs.…”
Section: Discussionsupporting
confidence: 49%
“…Baicalein inhibits CCAAT/enhancer binding protein b (C/EBPb) DNAbinding activity in COX-2 promoter region and suppresses COX-2 expression in mouse macrophages, 18) while C/EBPb plays no or little role in IL-6 and IL-8 transcription in LPStreated dermal fibroblasts and LPS-treated rheumatoid arthritis synovial fibroblasts. 22) Taken together, our results suggest that the mechanism of anti-inflammatory effects of TJ-9 is mainly the suppression of PGE 2 production rather than those of inflammatory cytokines. Moreover, this decreased PGE 2 production will cause substantial reduction of PGE 2 in periodontal tissue because periodontal tissue is mainly occupied by HGFs.…”
Section: Discussionsupporting
confidence: 49%
“…I B␣, in its wild-type or mutated forms, represents a specific inhibitor and has been used in experimental systems to inhibit NF-B activity. Such experiments have shown that TNF-␣ production by macrophages and expression of IL6 and IL8 in RA are NF-B dependent (13), that NF-B provides a link between inflammation and hyperplasia in RA joint (14), and that its inhibition results in TNF-␣-induced apoptosis of RA synovial fibroblasts (33). Also, in type I diabetes, NF-B inhibition protected human islet ␤ cells from the adverse effects of IL-1␤ (34).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of many proinflammatory genes is regulated by NF-B, such as the cytokines TNF-␣, IL-1␤, IL6, and IL8; adhesion molecules; matrix remodelling enzymes; cyclooxygenase-2; and inducible NO synthase. NF-B activity regulates expression of IL6 and IL8 in RA synovial fibroblasts (13) and links inflammation to hyperplasia in the arthritic joint (14). In addition, a peptide that inhibited nuclear localization of NF-B improved inflammatory disease in an animal model (15).…”
Section: Inhibition Of Nf-b Activity By a Membrane-transducingmentioning
confidence: 99%
“…Both p38 MAPK and NF-B have been reported to be implicated in the regulation of IL-6 expression (10,25). However, NF-B is essential as NF-B p50/p65-deficient fibroblasts do not express IL-6 in response to IL-1 (47). In our study, IL-1-induced IL-6 remained intact despite a profound reduction in IL-1-induced p38 phosphorylation in MIF Ϫ/Ϫ cells, and NF-B antagonism lead to near complete abrogation of IL-1-induced IL-6.…”
Section: Discussionmentioning
confidence: 99%